Are Proton Pump Inhibitors More Effective Than Histamine-2-Receptor Antagonists for Stress Ulcer Prophylaxis in Critically Ill Patients? A Systematic Review and Meta-Analysis of Cohort Studies. Issue 9 (September 2022) - He, Na; Yan, Yingying; Su, Shan; Ge, Qinggang; Zhai, Suodi
Background: Histamine-2-receptor antagonists (H2 RAs) have been largely replaced by proton pump inhibitors (PPIs) for stress ulcer prophylaxis (SUP) despite the inconclusive evidence concerning comparative effectiveness. Objective: To compare the effectiveness of PPIs and H2 RAs on SUP in real-world setting. Methods: PubMed, Embase, and the Cochrane Library were searched from inception to September 19, 2021. We included cohort studies comparing PPIs with H2 RAs in critically ill adult patients and explicitly reporting the outcome of gastrointestinal (GI) bleeding or mortality. Newcastle-Ottawa Scale was used to assess potential risk of bias. We conducted a random-effects meta-analysis and only the studies with adjusted effect estimates were pooled. The Grading of Recommendations Assessment, Development, and Evaluation system was used to assess the overall quality of the evidence. Results: Thirteen cohort studies (N = 145 149) were eligible and 11 of them available for full texts were of low to moderate risk of bias. Meta-analysis of adjusted effect estimates indicated that PPIs were associated with a significantly higher risk of GI bleeding, compared with H2 RAs (8 studies, odds ratio [OR] = 1.98, 95% confidence interval [CI] = 1.30-3.01, low certainty). Post hoc pooling analysis also suggested that PPIs were associated with a slightly higher risk of mortality in comparison with H2 RAs (7 studies, OR = 1.27, 95% CI = 1.13-1.42, low certainty). Conclusion and Relevance: The systematic review of cohort studies showed that PPIs were associated with higher risks of GI bleeding and mortality, although the certainty of evidence was low. Overall, we suggest not excluding H2 RAs for SUP, while further studies are essential for elucidating the risk stratification, optimal regimen, and specific duration.